2019
DOI: 10.1016/j.ajog.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms and surgical complications after opportunistic bilateral salpingectomy, a register-based cohort study

Abstract: BACKGROUND: In recent years, the fallopian tubes have been found to play a critical role in the pathogenesis of ovarian cancer. Therefore, bilateral salpingectomy at the time of hysterectomy has been proposed as a preventive procedure, but with scarce scientific evidence to support the efficiency and safety. OBJECTIVE: Our primary objective was to evaluate the risk of surgical complications and menopausal symptoms when performing bilateral salpingectomy in addition to benign hysterectomy. Furthermore, we sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…28 Our results conflict with a recent Swedish study in which women who underwent OS at the time of hysterectomy reported more menopausal symptoms 1 year after surgery than women who underwent hysterectomy alone. 29 If women in our cohort were experiencing menopausal symptoms differently according to OS status, they were not significant enough to change their care-seeking behaviors.…”
Section: Salpingectomymentioning
confidence: 95%
See 1 more Smart Citation
“…28 Our results conflict with a recent Swedish study in which women who underwent OS at the time of hysterectomy reported more menopausal symptoms 1 year after surgery than women who underwent hysterectomy alone. 29 If women in our cohort were experiencing menopausal symptoms differently according to OS status, they were not significant enough to change their care-seeking behaviors.…”
Section: Salpingectomymentioning
confidence: 95%
“…28 However, a recent Swedish Registry study found an increased risk of menopausal symptoms 1 year after hysterectomy among women who underwent hysterectomy with bilateral salpingectomy compared with hysterectomy alone (relative risk, 1.33; 95% confidence interval [CI], 1.04e1.69). 29 Given that an earlier age at menopause has been associated with increased mortality rates, 30e32 it is imperative that we understand whether OS decreases the age of onset of menopause. Herein, we use population-based data in British Columbia, Canada, to examine indicators of menopause, namely physician visits for menopause or the initiation of hormone replacement therapy (HRT) among women who undergo OS and women who undergo comparator surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish group recently published a retrospective observational cohort study using data from the National Quality Register of Gynecological Surgery in Sweden . The principal objective was to assess the likelihood of surgical complications and menopausal symptoms when performing bilateral salpingectomy as well as benign hysterectomy.…”
Section: Should We Be Performing Routine Salpingectomy As a Preventatmentioning
confidence: 99%
“…This has led to the introduction of the term "opportunistic salpingectomy", which is the removal of presumed healthy fallopian tubes at the time of other benign intra-abdominal surgery with ovarian preservation, with the aim of potentially preventing ovarian cancer [10]. Opportunistic salpingectomy at the time of hysterectomy for benign indication is considered feasible which is noted as a widespread uptake of the procedure around the world [10][11][12][13][14][15]. In spite of this apparent acceptance in clinical practice there is still no consensus.…”
Section: Introductionmentioning
confidence: 99%